Advanced trauma life support course for medical students. A new era? - Vassiliu, Panteleimon; Mavrogenis, Andreas; Theos, Christos; Koulouvaris, Panagiotis; Massalis, Ioannis; Geranios, Angelos; Bartsokas, Christos; Gerazounis, Michael; Tepetes, Konstantinos; Kamparoudis, Apostolos; Stergiopoulos, Spyros; Stavropoulos, Michael; et al. (Frontiers in Surgery, 2022)
Introduction Trauma represents a major public health issue and is one of the leading causes of death and disability worldwide. A systematic approach toward dealing with trauma patients was facilitated through the ATLS program, which has become a milestone in trauma care. Our new ATLS course for medical students was set in motion in 2015. Our aim was to make medical students familiar with trauma patients interactively, through a program like ATLS, and here we present the results of this endeavor. Methods A two-day ATLS-Medical Student (MS) course was offered from November 2015 to July 2018, and analysis was performed retrospectively on the data gathered over a three-month period through online questionnaires. Before graduating, 261 newly qualified medical doctors were interviewed and evaluated as part of the ATLS course. Results After the course, the vast majority of medical students (251 MSs; 96.16%) felt more capable of managing severely injured patients and 58% of students felt that the medical services they offered were better due to the ATLS training. Regarding the educational fee for the course, 56.7% of the students reported that they felt the fee of 100 euros was fair. Discussion The interactive format of the course, which differs from more traditional methods of teaching, has been endorsed by medical students. Though they lack clinical experience, that does not prohibit them from acquiring more specialized or specific knowledge, enabling them to excel. Most of the students improved their skillset either in theoretical knowledge, practical skills, or even in the emotional component of the course, i.e., dealing with treating a severely injured patient. It was decided that the program would be re-evaluated and extended to all Greek Medical Schools. Conclusion The advantage of providing doctors with trauma training at the beginning of their careers is evident. For that reason, it was decided that the program would be re-evaluated and extended to all Greek Medical Schools.